The Influence of Learning Media on Early Childhood Cognitive Development at KB IT Rabbani Pepao, Lekor Janapria - Suhaini (Journal of Islamic Religious Studies, 2025)
Early childhood is a crucial phase for cognitive development, requiring stimulating environments and appropriate instructional strategies. This study aimed to examine the types of learning media used and their influence on early childhood cognitive development at KB IT Rabbani Pepao, Lekor Janapria. Employing a quantitative descriptive approach, the research involved the total population of 38 children, using structured questionnaires and observation checklists to collect data. Descriptive statistics were used to analyze media usage trends, while simple linear regression determined the impact of media on cognitive outcomes. Findings indicated that picture cards (M=4.21, SD=0.62), storybooks (M=3.95, SD=0.75), and educational toys (M=3.68, SD=0.80) were the most commonly used media, whereas interactive digital media were used less frequently (M=2.47, SD=1.10). Cognitive assessment results showed higher mean scores in memory (M=78.5) than in reasoning (M=74.3) and problem-solving (M=70.1). Regression analysis revealed a statistically significant positive relationship between learning media usage and cognitive development (β = 0.62, p < 0.001), accounting for 38% of the variance. These findings suggest that the strategic use of varied media supports cognitive growth in young children, particularly in rural Islamic educational settings. The study underscores the need for integrating accessible and engaging media into early learning environments to enhance memory, reasoning, and problem-solving skills.